Philosophical Issues in Sport Science - Ryall, Emily (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The role and value of science within sport increases with ever greater professionalization and commercialization. Scientific and technological innovations are devised to increase performance, ensure greater accuracy of measurement and officiating, reduce risks of harm, enhance spectatorship, and raise revenues. However, such innovations inevitably come up against epistemological and metaphysical problems related to the nature of sport and physical competition. This Special Issue identifies and explores key and contemporary philosophical issues in relation to the science of sport and exercise. It is divided into three sections: 1. Scientific evidence, causation, and sport; 2. Science technology and sport officiating; and 3. Scientific influences on the construction of sport. It brings together scholars working on philosophical problems in sport to examine issues related to the values and assumptions behind sport and exercise science and key problems resulting from these and to provide recommendations for improving its practice.